PENGARUH KEBIJAKAN PUBLIK TERHADAP PENERAPAN TEKNOLOGI HIJAU DAN BLUE INNOVATION DALAM MENDUKUNG EKONOMI SIRKULAR - Handayani Harahap, Hastuti; Rudy Sentosa Rajagukguk, Frederick; Welly Arifin, Indra (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of public policy on the circular economy, both directly and through the mediating role of green technology adoption and blue innovation. The method employed is Partial Least Squares-Structural Equation Modeling (PLS-SEM), using primary data collected through a survey. The findings indicate that public policy has a positive and significant impact on the circular economy, both directly and indirectly through the application of green technology and blue innovation. The R-square value of 0.851 and the high T-statistics support these results. Therefore, implementing policies aligned with sustainable innovation is key to achieving a circular-based economic system. This study proves that public policy plays a significant role in encouraging the achievement of a sustainable circular economy system. The results of statistical tests show that public policy not only has a direct effect on the circular economy but also has an indirect effect through the mediating role of the application of green technology and blue innovation. The application of green technology and blue innovation has been shown to provide a significant contribution in strengthening the impact of public policy on the circular economy.